Investigation the effect of ramelteon on urinary bladder smoth muscle contraction-relaxation mechanism (Annals of Medical Research, 2022)
Aim and BackgroundA melatonin receptor agonist Ramelteon is a drug that is also used in urinary tract infections. Melatonin is known to have an effect on smooth muscle contraction. In this study, we aimed to question whether ramelteon exerts a melatonin-like effect on bladder contractions.Material Methods Wistar-albino (n = 8) intact female rats were used in the study. After decapitation, 1.5x5 mm bladder strips were examined in an isolated organ bath in which there was Krebs-Henseleit solution. After the regulation period, ramelteon was applied non-cumulatively in two separate doses of 0.2μM, 1μM. The area under the curve (AUC) and peak to peak (p-p) values ​​before and after the application were normalized as% change.Results Exposure of bladder strips to ramelteon significantly increased contractions. Ramelteon caused a statistically significant increase in p-p, AUC values ​​of spontaneous bladder contractions at a dose of 0.2 and 1μM (P
Keywords: Ramelteon; Urinary Bladder; Isometric Contraction; Rat